Clinical Profile of Metabolic Derangements in Patients with Acute Exacerbations of Chronic Obstructive Pulmonary Disease - Aryal, Saroj Babu; Panthi, Akriti; Aryal, Nadira; Risal, Bijay (Journal of Nepal Health Research Council, 2025)
Background: Chronic obstructive pulmonary disease is defined as a preventable and treatable disease characterized by persistent respiratory symptoms and airflow limitation attributable to airway accompanied by alveolar abnormalities elicited by significant exposure to noxious particles or gases. Stress hormone is involved in proclivity towards causation of hyperglycemia and hyponatremia in COPD. Methods: This study is an analytical cross sectional single center study that was carried out in Tribhuvan University Teaching Hospital. Specimens were processed as per the guidelines of Standard Operating Procedure (SOP) of Biochemistry laboratory of Tribhuvan University Teaching Hospital. Results: In this study of 138 patients with acute exacerbation of COPD, the mean age was (71.88±9.771) years with higher prevalence in the age group between 70-80 years of age. Females (65.2%) outnumbered males and 71.7% came from outside the Kathmandu valley. Hyponatremia was observed in sodium levels with 51.4% below normal with majority of patient’s possessing mixed acid-base disorders (58.7%). Most of thepatients 76.5% received general care with a mean hospital stay of 8.7 days. Statistical analysis revealed significant associations between care type, geographical distribution (p=0.026) and duration of stay with care type (p=0.0001). No significant associations were found regarding gender, glucose, sodium, potassium levels and age with duration of stay. Conclusions: Factors such as age, gender, and glycemic status did not significantly affect the type of care or duration of hospital stay, geographical location emerged as a significant determinant, with patients from outside the Kathmandu valley more likely to receive general care. Despite the prevalence of electrolyte imbalances and acid-base disorders, these biochemical factors showed no substantial impact on clinical outcomes, suggesting that other factors may play a more significant role in duration of stay. Keywords: Acid-base imbalance; biochemistry; glucose; potassium; pulmonary.